District Credit Plan 1988-90 and Annual Action Plan 1988 District Raigarh(M.P.) - Planning Commission (Planning Commission, 1988)
The district predominates with mixed black, red and yellow soil of archian dhoriwarian origin. The marshy lands are generally found in valley and are plain (locally called ’Bahia' land), medium type of soil (Sandy loam) are found in the basin of rivers and are locally known as 'Matasi' or 'Kanhar', and; light soil (Sandy and Stoney) are found in the upland of the area of the district which are locally known as 'Tand' or ' Tikra. No special soil problems such as acidity, alkanity or salinity exists in the district.
Madhya Pradesh